Pengaruh Dewan Komisaris Independen, Komite Audit, Good Corporate Governance, dan Kinerja Keuangan terhadap Pengungkapan Sustainability Report: Studi pada Perusahaan BUMN yang Terdaftar di IDX-MES BUMN 17 Tahun 2021-2024 - Idu Aulia; Zuliansyah, Zuliansyah; Yusuf Bachtiar (Journal of Economic and Business Advancement, 2026)
The disclosure of Sustainability Reports by State-Owned Enterprises (SOEs) plays an important role not only in complying with regulatory requirements, but also in building the company's image and stakeholder trust. This study aims to analyze the influence of Good Corporate Governance and financial performance on the disclosure of Sustainability Reports in SOEs listed on the IDX-MES BUMN 17 index for the period 2021–2024. The research sample consisted of 9 companies with a total of 36 observations obtained through purposive sampling. Data analysis was performed using descriptive statistics, classical assumption tests, and hypothesis testing with the help of Microsoft Excel and SPSS version 22. The results show that Good Corporate Governance and financial performance influence Sustainability Report disclosure, while independent boards of commissioners and audit committees do not. Simultaneously, all research variables have a significant effect on Sustainability Report disclosure.